2019
DOI: 10.1101/658492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cohesin loader NIPBL interacts with pre-ribosomal RNA and treacle to regulate ribosomal RNA synthesis

Abstract: NIPBL is an essential loader of cohesin to mediate sister chromatid cohesion and chromatin loop organization. NIPBL mutations cause Cornelia de Lange Syndrome. How NIPBL's genomic localization is specified is not fully understood. We found that NIPBL localizes to the nucleolus in an RNA-dependent manner and binds directly to ribosomal RNA (rRNA). We identified two RNA binding domains in NIPBL in vitro, both of which are required for efficient rRNA binding in vivo. NIPBL binds to ribosomal DNA (rDNA) in an RNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Its direct role in Pol I–dependent transcription is not clear ( Lin and Yeh, 2009 ). Furthermore, an increasing number of studies have reported the role of Treacle in recruitment and/or retention of different nonnucleolar proteins in nucleoli ( Fages et al, 2020 ; Kong et al, 2019 ; Larsen et al, 2014 ; Mooser et al, 2020 ; Rawlinson et al, 2018 ; Velichko et al, 2019 ). It is clear that Treacle can interact with BRCT-containing factors ( Larsen et al, 2014 ; Mooser et al, 2020 ; Velichko et al, 2019 ); however, it is not known whether Nbs1 and TOPBP1 are the only BRCT proteins that interact with Treacle.…”
Section: Discussionmentioning
confidence: 99%
“…Its direct role in Pol I–dependent transcription is not clear ( Lin and Yeh, 2009 ). Furthermore, an increasing number of studies have reported the role of Treacle in recruitment and/or retention of different nonnucleolar proteins in nucleoli ( Fages et al, 2020 ; Kong et al, 2019 ; Larsen et al, 2014 ; Mooser et al, 2020 ; Rawlinson et al, 2018 ; Velichko et al, 2019 ). It is clear that Treacle can interact with BRCT-containing factors ( Larsen et al, 2014 ; Mooser et al, 2020 ; Velichko et al, 2019 ); however, it is not known whether Nbs1 and TOPBP1 are the only BRCT proteins that interact with Treacle.…”
Section: Discussionmentioning
confidence: 99%
“…The possession of more than a single RBD could theoretically allow RBPs to be multifunctional, for instance through the separate regulation of different sets of targets (Kong et al, 2019). Multifunctionality may additionally be established through the condition- or cell type-specific expression of RBPs and their interaction partners, or through dynamic shuttling of RBPs between different subcellular compartments, such as the nucleus and cytosol (Dassi, 2017; Díaz-Muñoz & Turner, 2018; Gray et al, 2015; Yugami et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The possession of more than a single RBD would theoretically allow RBPs to be multifunctional, for instance through the separate regulation of different sets of targets (Kong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…centromeres, rDNA), selected Topological Associated Domain (TAD) boundaries and gene promoters. The top hits for selected loci contain well-characterized locus- specific proteins and proteins that have only recently been identified in association with specific loci, such as NIPBL and RNA polymerase II for rDNA 22, 23 , and GTF2I and BRD4 for TAD boundaries 24, 25 (Fig. 1c and 1d).…”
Section: Introductionmentioning
confidence: 99%